2005
DOI: 10.1080/10683160500256743
|View full text |Cite
|
Sign up to set email alerts
|

Seclusion and the use of antipsychotics in hospitalized psychiatric patients

Abstract: The purpose of this study is to measure the incidence of seclusion, identify possible determinants of seclusion and to gain insight into the use of antipsychotics before and after seclusion in acutely admitted patients. In The Netherlands, special treatment methods including seclusion and involuntary medication may only be applied in involuntarily hospitalized patients in cases of danger to the patient or others, with exclusion of emergencies. Data were retrospectively collected over the years 1997 Á/1999 from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 12 publications
3
17
0
Order By: Relevance
“…Significant results were found for age, with secluded patients tending to be younger than those who were not secluded. This is consistent with the findings from other research from New Zealand (El‐Badri & Mellsop 2002), the United Kingdom (Morrison & Lehane 1996), Norway (Sorgaard 2004), the Netherlands (Stolker et al. 2005), the United States (Smith et al.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Significant results were found for age, with secluded patients tending to be younger than those who were not secluded. This is consistent with the findings from other research from New Zealand (El‐Badri & Mellsop 2002), the United Kingdom (Morrison & Lehane 1996), Norway (Sorgaard 2004), the Netherlands (Stolker et al. 2005), the United States (Smith et al.…”
Section: Discussionsupporting
confidence: 92%
“…No research could be located that measured the relationship between HoNOS scores and seclusion. However, Stolker et al. (2005) used the Global Assessment of Functioning Scale to measure social, psychological and occupational function, and found an association between seclusion and lower levels of functioning according to this scale.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in the law mean that countries vary in their use of formal restraint [7,13,28]. In the Netherlands, psychiatrists prefer seclusion to forced medication [26,29]; while in some other countries psychiatrists regard seclusion as the most restrictive intervention [7,[30][31][32][33].…”
Section: Professionals' Attitudes: Relationships and Interpretationsmentioning
confidence: 99%
“…One study of almost 1000 in-patients in The Netherlands (Stolker 2005) found a close correlation between scores on the Global Assessment of Functioning (GAF) scale and seclusion. Scores < 55 were correlated with higher seclusion rates, and the lower the score, the stronger the correlation.…”
Section: Characteristics Of Secluded Patientsmentioning
confidence: 99%